Analisis Penerapan Metode Simpleks Pemrograman Linier Kasus Maksimasi Pada Usaha Dimsum Delights - Pesta Gultom; Arelina Br Ginting; Almerisa Novianti Br Tarigan; Mariani Ginting; Netrika Sari Zalukhu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This report examines the critical challenge faced by Small and Medium Enterprises (UMKM) in the culinary sector: optomizing production to achieve maximum profit amidst limited resources. Linear Programming (LP) and teh Simplex Method are introduced as robust quantitave tools to address this problem. The primary objective of this study is to analyze and apply the Simpleks Method to determine the optimal production quantities for “Dimsum Delights” products, thereby maximizing their daily profit. Utilizing a quantitative approach, data on raw material consumption, capacities, and product profitability are hypothetically established and processed through manual simpleks calculations. This demonstrates the Simpleks Method′s practically utility in empowering culinary UMKM to transition from intuitive decision-making to a data-driven approach, fostering enhanced eficiency and profitability.